Estimating trends in US income inequality using the current population survey: the importance of controlling for censoring - Richard V. Burkhauser; Shuaizhang Feng; Stephen P. Jenkins; Jeff Larrimore (Institute for the Study of Labor (IZA), 2008)
Using internal and public use March Current Population Survey data, we analyze trends in US income inequality (19752004). Using a multiple imputation approach where values for censored observations are imputed using draws from a Generalized Beta distribution of the Second Kind, we find that the upward trend in income inequality significantly slowed after 1993. Our results closely match the income share trends reported by Piketty and Saez (2003) except for within the top 1 percent of the distribution. Thus, we argue that if inequality has increased substantially since 1993, such increases are confined to this very high income group.
urn:nbn:de:101:1-2008100913
Keywords: D31; 330; US income inequality; time trend; CPS; censoring; topcoding; inequality; Einkommensverteilung; Soziale Ungleichheit; Messung; Statistische Erhebung; Statistische Methode; USA